Laparoscopic Gynecological Surgery in Bharatpur Hospital: An Experience from a Government Tertiary Care Center of Central Nepal - Adhikari, Shree Prasad; Pariyar, Jewan; Poudel, Sandesh; Poudel, Atit; Jha, Anamika (Journal of College of Medical Sciences-Nepal, 2020)
Background: The aim of the study was to share the experience of laparoscopic gynecologic surgery in a government hospital outside Kathmandu valley Method: A descriptive cross-sectional study was carried out in Bharatpur Hospital from 15 Dec, 2018 to 15 June, 2019. Fifty consecutive patients who underwent laparoscopic gynecological procedures were included in the study and analyzed demographics, indication, hospital stay and complications. Results: The mean age of the patients (n = 50) was 34.6 ± 12.5 years (Range: 17 – 66 years). More than athird of the total patients (n = 18, 36.0%) were between 26 – 35 years. Majority (n = 26, 56.0 %) of the patients were multipara (≥ 2 child). Hasson type was more frequently utilized type of primary port incision in the surgeries performed (52.0%, n = 26). The median duration of surgery was 2.08 hours (Range: 0.83 – 3.25 hours). The commonest post-operative diagnosis was dermoid cyst (n = 14, 28.0%). Complications were observed in eight patients (16.0 %). The median duration of post-operative hospital stay was 3 days. Conclusions: LGS has evolved greatly advantageous as it reduces hospital stay, surgical site infection, and better aesthetic results. It is essential to extend services outside the Kathmandu Valley